(untitled) (Global Journal of Human-Social Science, 2022)
On the occasion of two research in Popular Education in different fields and from two university institutions such as the Autonomous University of Madrid and the National University of Entre R os deconstructive processes of liberation in Latin American spaces are known At the same time the link to a research group in Health Inclusions Equity and Pedagogy allows a complementarity towards meanings and socio-historical stories In a timeline between 2003 and 2014 formative experiences with liberating projections are identified These experiences take stories from spaces in countries such as Mexico Costa Rica Uruguay and Argentina The main objectives are focused on the identification of the pedagogical processes from the documentary testimonies of the experiences The analyzes have dimensions of gender perspective technological appropriation and ways of doing things The dominant official story is dismantled from its denaturalization new stories arise typical of the context-pedagogical process relationship and historical analysis